1993
DOI: 10.1523/jneurosci.13-03-01202.1993
|View full text |Cite
|
Sign up to set email alerts
|

A PET study of visuospatial attention

Abstract: Positron emission tomography (PET) was used to identify the neural systems involved in shifting spatial attention to visual stimuli in the left or right visual field along foveofugal or foveocentric directions. Psychophysical evidence indicated that stimuli at validly cued locations were responded to faster than stimuli at invalidly cued locations. Reaction times to invalid probes were faster when they were presented in the same than in the opposite direction of an ongoing attention movement. PET evidence indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

113
761
13
18

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,439 publications
(908 citation statements)
references
References 59 publications
113
761
13
18
Order By: Relevance
“…The more inferior medial activation of the precuneus corresponds closely to areas reported previously to be active during spatial attention and spatial working memory tasks [Corbetta et al, 1993;Giesbrecht et al, 2003;Owen et al, 1996] as well as during temporal orienting and combined spatial and temporal orienting [Coull and Nobre, 1998]. We propose that, together with the SPL, it serves to maintain a spatiotemporal bias against to-be-ignored locations, in favor of to-be-searched locations.…”
Section: Discussion Previewsupporting
confidence: 84%
See 1 more Smart Citation
“…The more inferior medial activation of the precuneus corresponds closely to areas reported previously to be active during spatial attention and spatial working memory tasks [Corbetta et al, 1993;Giesbrecht et al, 2003;Owen et al, 1996] as well as during temporal orienting and combined spatial and temporal orienting [Coull and Nobre, 1998]. We propose that, together with the SPL, it serves to maintain a spatiotemporal bias against to-be-ignored locations, in favor of to-be-searched locations.…”
Section: Discussion Previewsupporting
confidence: 84%
“…Exactly how the parietal cortex should be subdivided functionally remains an important question. Traditionally, the SPL has been assigned a role in spatial processing, but also in implementing expectations (which emphasizes its temporal character) [Corbetta et al, 1993;Coull and Nobre, 1998;Hopfinger et al, 2000;Kastner and Ungerleider, 2000;Owen et al, 1996;Posner et al, 1984]. Others have found the more inferior and lateral intraparietal sulcus (IPS) as the main source of spatial or temporal selection-related activation (sometimes alongside SPL activation) [Coull and Nobre, 1998;Gitelman et al, 1999;Hopfinger et al, 2000;Kanwisher and Wojciulik, 2000;Marois et al, 2000;Owen et al, 1996;Shulman et al, 1999;Vandenberghe et al, 2000; for monkey IPS see also Gottlieb et al, 1998].…”
Section: Posterior Parietal Functionmentioning
confidence: 99%
“…These areas become activated in response to sustained attention in multisensory as well as visual, somatosensory, and auditory experimental setups (Pardo et al, 1991;Paus et al, 1997). The right posterior parietal cortex is involved in attentional orientation to locations (PET: Corbetta et al, 1993;Nobre et al, 1997) and is considered critical for forming a multimodal sensory representation of the extrapersonal space (Mesu- lam, 1981). Earlier brain activation studies reported that the FEF and SMA (including SEF) are also involved in visuospatial attentional tasks (Nobre et al, 1997;Coull et al, 1996) and that the thalamus is implicated in sustained attention (PET: Kinomura et al, 1996;Paus et al, 1997).…”
Section: An "Exteroceptive Mental State" (Eyes Open ͼ Eyes Closed)?mentioning
confidence: 99%
“…De Leon et al (2001) also recently reported that ApoE-ɛ4 carriers without dementia who declined to a diagnosis of AD over a 3-year period showed pronounced metabolic decline longitudinally in the temporo-parietal cortex. Furthermore, regional blood flow in the parietal cortex-but in no other brain region-has been shown to predict years of survival of AD patients (Jagust, Haan, Reed, & Eberling, 1998).Second, the posterior parietal cortex and subcortical structures form a distributed neural network that is involved in attentional shifting (Mesulam, 1981;Posner & Petersen, 1990), as revealed by single-unit studies in monkeys (Bushnell, Goldberg, & Robinson, 1981;Robinson et al, 1995) and human neuroimaging studies (Corbetta et al, 1993). A recent fMRI study found the inferior parietal/superior temporal area to be specifically involved in the disengage component of attentional shifting (Corbetta et al, 2000).…”
mentioning
confidence: 99%